Comparasion of Self Confidence Levels Between Active and Inactive Students in Extracurricular Activities - Desi Nurian Sari; Lira Erwinda; Nurul Fajri (Journal of Behavioral Innovation, 2026)
Understanding students’ confidence is important, as it affects their academic performance, social interactions, and personal growth, which may be influenced by their involvement in extracurricular activities. This study aims to compare the level of confidence between active and inactive students in extracurricular activities at SMPN 277 Jakarta. This study used a quantitative approach using a comparative method. The population in this study was class VIII students of SMPN 277 Jakarta which numbered 250 students and samples were taken using Isaac and Michael's tables. The research instrument is a Likert scale questionnaire that measures confidence. Data analysis includes descriptive statistics, validity and reliability tests, normality and homogeneity tests, and t-Independent tests. Research results show that involvement in extracurricular activities positively affects students' increased confidence, implying that schools need to further encourage students' participation in these activities as a means of psychological and social development.